Probiotics and MicroRNA: Their Roles in the Host–Microbe Interactions - Zhao, Ying; Zeng, Yan; Zeng, Dong; Wang, Hesong; Zhou, Mengjia; Sun, Ning; Xin, Jinge; Khalique, Abdul; Rajput, Danish Sharafat; Pan, Kangcheng; Shu, Gang; Jing, Bo; et al. (Frontiers in Microbiology, 2021)
Probiotics are widely accepted to be beneficial for the maintenance of the gut homeostasis - the dynamic and healthy interactions between host and gut microorganisms. In addition, emerging as a key molecule of inter-domain communication, microRNAs (miRNAs) can also mediate the host-microbe interactions. However, a comprehensive description and summary of the association between miRNA and probiotics have not been reported yet. In this review, we have discussed the roles of probiotics and miRNAs in host-microbe interactions, and proposed the association of probiotics with altered miRNAs in various intestinal diseases and potential molecular mechanisms underlying the action of probiotics. Furthermore, we provided a perspective of probiotics - miRNA - host/gut microbiota axis applied in search of disease management highly associated with the gut microbiome, which will potentially prove to be beneficial for future studies.